Low inter-diffusivity γ'-base bondcoats for single crystal superalloy René N5. I: Primary study of microstructures and oxidation behaviors at 1100 ºC. (February 2019) - Yao, Hongrui; Yang, Lanlan; Bao, Zebin; Zhu, Shenglong; Wang, Fuhui
Highlights: The crystalline structure of the as-sputtered coatings is fcc γ'-Ni3 Al phase with preferential orientation [111]. The annealed coatings consist of γ' matrix with a few dispersed TCP and different volume percent of β-NiAl. The γ' coatings exhibited excellent oxidation resistance at 1100 °C due to the formation of α-Al2 O3 scales. The interdiffusion behaviors between the γ' coatings and René N5 substrates was analyzed. Abstract: Three γ'-base bondcoats, which are referred to as Al-19, Al-20 and Al-25 following their atomic percent of Al, respectively, were prepared on single crystal superalloy René N5 by magnetron sputtering. All the coatings exhibited excellent resistance against high temperature oxidation at 1100 °C. Furthermore, the coatings Al-19 and Al-20 exhibited low inter-diffusivity to the substrate, neither interdiffusion zone nor secondary reaction zone was formed during oxidation at 1100 °C for 300 h. A secondary diffusion zone was observed in the Al-25 coated samples probably due to precipitation of ∼11.4 vol.% β-NiAl in the coating during vacuum annealing at 1000 °C.